PENGARUH KARAKTERISTIK SOSIAL EKONOMI PETANI TERHADAP KETERSEDIAAN PANGAN RUMAH TANGGA PETANI DI KECAMATAN WARUDOYONG KOTA SUKABUMI - Tuti Gantini; Euis Dasipah; Nataliningsih Nataliningsih; Nugroho Budi Rahayu (Postgraduate, University of Mataram, 2024)
Food security is a global, multidimensional issue with social, economic, political and environmental interests. The purpose of this study was to determine the influence of socioeconomic characteristics of farmers on the availability of farm household food in Warudoyong Sub-district, Sukabumi City. This study used descriptive method with quantitative approach. The data collection techniques used in this research are observation, questionnaires, literature, and documentation. The results showed that the socio-economic characteristics of farmers, which include age, education, area of cultivated land, number of dependents, and farmers' income, together have a significant effect on the food availability of farming families with a contribution of 97.8%, while 2.2% is influenced by other variables outside the study. Farmers' age through education has a significant effect on food availability, but farmers' education through income does not have a significant indirect effect. Similarly, the size of cultivated land through income also has no significant effect on family food availability. The direct effect of these factors is greater than the indirect effect, so the income variable is not a significant mediator in the relationship between education and land area on food availability. The implication of this study is that the increasing age of farmers will further reduce the food availability of farming families.